Effect Of The Addition Of VCO (Virgin Coconut Oil) Oil In Clay Mask Formulation Alfa-Tocoferol As Anti-Aging - Monica Suryani; Suharyanisa Suharyanisa; Jon Kenedy Marpaung (Sean Institute, 2023)
Premature aging is a natural process in life. Usually premature aging is caused by excessive sun exposure, pollution, and stress. Vitamin E and lauric acid and oleic acid from VCO oil as antioxidant that can protect the skin from free radicals and which work as maoisturizers to prevent dry skin. to formulate and evaluate clay mask preparations from alpha-tocopherol and vco oil as anti-aging. this research was conducted experimentally. The preparations of Clay mask was carried out by adding alpha-tocopherol and vco oil with concentrations of 1%:5% (F1), 1%:7% (F2), and 1%:9% (F3) respectively into the base of the clay mask and preparations. The blank (F0) was used as a clay mask base witout the additionof alpha-tocopherol and Vco oil. Tests on clay mask preparations include homogeneity test, stability test, pH test, irritation test, mask drying time test and anti-aging effectiveness measurement test using a skin analyzer on volunteers‟ faces. Parameters tested include water content, large pores, many blemishes and wrinkles. The treatment was carried out for four weeks. the results of the study showed that alpha-tocopherol and vco oil could be formulated in clay mask preparations and werw stable for 12 weeks of storage, homogeneous mask preparations, pH 5,6-6,1, stable during storage, could not irritate the skin. The higher the concentration used indicates a change in skin condition for the better with the highest concentration for four weeks for thr better with increasing water content (22,33 to 40,66), smaller pore (39,66 to 20,00), reduced blemishes (40,66 to 21,00), less wrinkles (34,00 to 16,00). alpha-tocopherol with vco oil can be formulated into a clay mask preparation and its good effevtiveness as an anti-aging can be seen in clay mask with 9% vco oil concentration. Imparoved skin condition with increased moisture content (percent recovery 33,54%), smaller pores (prcent recovery 45,96%), reduced blesmishes (percent recovery 49,11%) and reduced wrinkles (percentage recovery 44,85%). However, for some people, using a clay mask can cause allergic reactions and itching. In addition, excessive use of clay masks can also make the skin dry, which triggers excess oil production. It is hoped that future researchers will be able to make clay mask formulas with different samples.